1988
DOI: 10.1038/clpt.1988.83
|View full text |Cite
|
Sign up to set email alerts
|

Induction of migrainelike headaches by the serotonin agonist m-chlorophenylpiperazine

Abstract: In a study of serotonin (5-HT) function in patients with eating disorders and healthy control subjects, severe headaches with features of common migraine occurred unexpectedly in 28 of 52 subjects (54%) 8 to 12 hours after receiving a single oral dose of the 5-HT receptor agonist m-chlorophenylpiperazine (m-CPP), 0.5 mg/kg. None of the same subjects developed similar late-occurring headaches after placebo or the 5-HT precursor, L-tryptophan, 100 mg/kg given intravenously. The frequency of these migrainelike he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(67 citation statements)
references
References 0 publications
0
67
0
Order By: Relevance
“…A role has been proposed for the 5-HT2C receptor since the 5-HT2A preferential antagonist, ketanserin, is not effective (39). This assumption is further supported by the observation that the 5-HT2C agonist, mCPP, triggers migraine attacks (40). Nevertheless, only trace amounts of 5-HT2C receptor mRNA are detected in meningeal tissues.…”
Section: Discussionmentioning
confidence: 51%
“…A role has been proposed for the 5-HT2C receptor since the 5-HT2A preferential antagonist, ketanserin, is not effective (39). This assumption is further supported by the observation that the 5-HT2C agonist, mCPP, triggers migraine attacks (40). Nevertheless, only trace amounts of 5-HT2C receptor mRNA are detected in meningeal tissues.…”
Section: Discussionmentioning
confidence: 51%
“…In a now classic paper, Brewerton et al [19] found that the trazadone metabolite metachlorophenylpiperazine (mCPP) would trigger headaches in some patients with a previous history of migraine, though it is unclear from this report whether this applies to only a proportion of migrainous subjects. There is increasing evidence that this substance has significant agonist pharmacological activity at 5HT 2 receptor sub-types, particularly as the response is blocked by the serotonin antagonist metergoline [20].…”
Section: Red Wine Sensitivitymentioning
confidence: 53%
“…Before the characterisation of 5-HT2 subtypes, it was believed that their efficacy was due to 5-HT 2 Nevertheless, pizotifen, cyproheptadine, and methysergide are potent 5-HT 2B and 5-HT 2C receptor antagonists, while mCPP, an agonist of these, can induce migraine [13,14]. These three drugs, along with amitriptyline, propanolol, ketanserin, ritanserin, and mianserin, do not discriminate between 5-HT 2B and 5-HT 2C sites [15].…”
Section: Serotonin and Migrainementioning
confidence: 99%